Aplicación de una auditoría tributaria en la cooperativa de ahorro y crédito “kullki wasi” ltda., en la provincia de Tungurahua, cantón Ambato, en el periodo 1 de enero al 31 de diciembre del 2012 - Bautista Cando, Miryan Elizabeth (2015)
The present research aimed to conduct a study on tax obligations in order to meet compliance with the Internal Revenue Service. The purpose of the research was to conduct a Tax Audit Cooperative Savings and Credit Kullki Wasi Ltda., To verify the reasonableness of the information reflected in the financial statements, tax returns, forms and transactional annexes, as a means of making decision allowing maximum efficiency and effectiveness in its activities the entity, for which methods for gathering information such as the survey was applied, interviews, observation, audit methods and techniques. Application of Tax Audit helped establish if they are reasonably applied accounting standards, if correctly interpreted the tax laws within the cooperative and consequently if you have completed all tax returns which is subject to the financial institution.